Object-oriented wavefront correction in an asymmetric amplifying high-power laser system. (14th March 2018) - Yang, Ying; Yuan, Qiang; Wang, Deen; Zhang, Xin; Dai, Wanjun; Hu, Dongxia; Xue, Qiao; Zhang, Xiaolu; Zhao, Junpu; Zeng, Fa; Wang, Shenzhen; Zhou, Wei; et al.
Abstract: An object-oriented wavefront control method is proposed aiming for excellent near-field homogenization and far-field distribution in an asymmetric amplifying high-power laser system. By averaging the residual errors of the propagating beam, smaller pinholes could be employed on the spatial filters to improve the beam quality. With this wavefront correction system, the laser performance of the main amplifier system in the Shen Guang-III laser facility has been improved. The residual wavefront aberration at the position of each pinhole is below 2 µ m (peak-to-valley). For each pinhole, 95% of the total laser energy is enclosed within a circle whose diameter is no more than six times the diffraction limit. At the output of the main laser system, the near-field modulation and contrast are 1.29% and 7.5%, respectively, and 95% of the 1 ω (1053 nm) beam energy is contained within a 39.8 µ rad circle (6.81 times the diffraction limit) under a laser fluence of 5.8 J cm −2 . The measured 1 ω focal spot size and near-field contrast are better than the design values of the Shen Guang-III laser facility.